The use of expressive methods for developing empathic skills - (:unkn) unknown (My University, 2011)
Empathy is one of the fundamental concepts in nursing, and it is an ability that can be learned. Various education models have been tested for improving empathic skills. Research has focused on using oral presentations, videos, modeling, practiced negotiation based on experiences, and psychodrama methods, such as role playing, as ways to improve empathy in participants. This study looked at the use of expressive arts to improve empathic skills of nursing students. The study was conducted with 48 students who were separated into five different groups. All groups lasted for two hours, and met for 12 weeks. Expressive art and psychodrama methods were used in the group studies. The Scale of Empathic Skill was administered to participants before and after the group studies. Before the group study took place, the average score for empathic skill was 127.97 (SD = 21.26). After the group study, it increased to 138.87 (SD = 20.40). The average score for empathic skill increased after the group (t = 3.996, p = .000). Results show that expressive methods are easier, more effective, and enjoyable processes in nursing training. © 2011 Informa Healthcare USA, Inc.